Understanding Autoplagiarism, Its Relevance and Challenges in Occupational Medicine - Ratih Setiawati (The Indonesian Journal of Community and Occupational Medicine, 2026)
Background: Autoplagiarism, also known as self-plagiarism or text recycling, is a form of plagiarism where an individual reuses their ownscientific work without appropriate attribution. In fields like medicine, including occupational medicine, the integrity of scientific publicationsis crucial because it influences the quality of the evidence guiding clinical practice and occupational health policies.Methods: This study is a narrative review that reflects the understanding of self-plagiarism. Articles were obtained through searches on onlinedatabases such as Google Scholar, PubMed, ProQuest, and other open sources, published between 2019 and 2026.Results: Autoplagiarism includes behaviors such as reusing text, duplicate publication, study fragmentation (salami slicing), and publishingupdated work without proper references. Research involving students and medical professionals indicates that there is still a limitedunderstanding of this particular issue. The advancement of digital technologies and artificial intelligence (AI) introduces new challenges fordefining autoplagiarism as well as opportunities for identifying it. Ethically, autoplagiarism remains disapproved by standards such as theCommittee on Publication Ethics (COPE) and the European Code of Conduct for Research Integrity, but it remains relatively unregulatedlegally in many regions. However, there are multiple approaches involving multiple parties, even also by utilizing artificial intelligence (AI)technology, to minimize and avoid such plagiarism.Conclusions: Despite the ongoing debate, autoplagiarism is considered a serious form of ethical and scientific misconduct in medical research.Understanding the concept and consequences of autoplagiarism is important when publishing manuscripts to actively avoid misconduct,whether intentional or not. An attempt to improve academic awareness, alongside active collaboration among institutions, publishers,regulatory bodies, and individual researchers, is important for tackling these challenges.